Holocene Glacier Fluctuations in the Torngat Mountains, Northern Labrador - McCoy, William (Géographie physique et Quaternaire, 1983)
ABSTRACTLichen measurements and other relative-age data were collected from deposits of several cirque glaciers in the Torngat Mountains of northern Labrador. Lichen growth stations were established, but no lichen-growth curve has yet been determined for the local area. However, moraines can be correlated between valleys on the basis of the largest diameter thallus of Rhizocarpon geographicum sensu lato combined with other relative-age data. These data suggest several discrete periods of Holocene glacier recession. If the R. geographicum s. I. growth curve established for the northern Cumberland Peninsula of Baffin Island (MILLER, 1975) is valid for similar environments in the Torngat Mountains, then glacier recession occurred < 150, 400, 550-750, 950, ≥ 1850, > 1850, ≥ 2800, > 2800, ≥ 4000, and > > 4000 yr BP. The latest three periods of glacier recession may correlate with periods of glacier recession on the Cumberland Peninsula of Baffin Island.